Extramural vascular invasion nomogram before radical resection of rectal cancer based on magnetic resonance imaging - Tian, Lianfen; Li, Ningqin; Xie, Dong; Li, Qiang; Zhou, Chuanji; Zhang, Shilai; Liu, Lijuan; Huang, Caiyun; Liu, Lu; Lai, Shaolu; Wang, Zheng (Frontiers in Oncology, 2023)
Purpose: This study verified the value of magnetic resonance imaging (MRI) to construct a nomogram to preoperatively predict Extramural vascular invasion (EMVI) in rectal cancer using MRI characteristics. Materials and Methods: There were 55 rectal cancer patients with EMVI and 49 without EMVI in the training group. The external validation group consisted of 54 rectal cancer patients with EMVI and 55 without EMVI. High-resolution rectal T2WI, pelvic diffusion-weighted imaging (DWI) sequences, and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) were used. We collected the following data: distance between the lower tumor margin and the anal margin,distance between the lower tumor margin and the anorectal ring, tumor proportion of intestinal wall, mrT stage, maximum tumor diameter, circumferential resection margin, superior rectal vein width, apparent diffusion coefficient(ADC), T2WI EMVI score, DWI and DCE-MRI EMVI scores, demographic information, and preoperative serum tumor marker data. Logistic regression analyses were used to identify independent risk factors of EMVI. A nomogram prediction model was constructed. Receiver operating characteristic curve analysis verified the predictive ability of the nomogram. P < 0.05 was considered signficant. Result: Tumor proportion of intestinal wall, superior rectal vein width, T2WI EMVI score, and carbohydrate antigen 19-9 were significant independent predictors of EMVI in rectal cancer and were used to create the model. The areas under the receiver operating characteristic curve, sensitivities, and specificities of the nomogram were 0.746, 65.45%, and 83.67% for the training group, respectively, and 0.780, 77.1%, and 71.3% for the external validation group, respectively. Data Conclusion: A nomogram including MRI characteristics can predict EMVI in rectal cancer preoperatively and provides a valuable reference to formulate individualized treatment plans and predict prognosis. Keywords: nomogram, rectal cancer, magnetic resonance imaging, extramural vascular invasion, tumor markers